Выбор основных параметров вихревого диода для предотвращения гидравлических ударов в вертикальных трубопроводах - Кононенко, Анатолий Петрович; Овсянников, Владимир Павлович; Оверко, М. В. (НТУ "ХПИ", 2014)
Наиболее часто мощные вертикальные трубопроводы применяются на шахтных водоотливных установках. Опасный гидравлический удар возникает в них при внезапном отключении насоса. В этих условиях средством защиты от опасных колебаний давления может быть гидравлический диод, установленный, например, в середине трубопровода. Наиболее приемлемым типом диода выбран вихревой струйный диод. Трудностью при моделировании переходного процесса в вертикальном трубопроводе с вихревым диодом является его существенная инерционность. Задача была решена с помощью локальной системы координат, которая вводится в программу расчета на время существования обратного тока жидкости. Используя разработанную модель можно определить размеры вихревого диода и рассчитать энергетические потери, которые могут возникнуть при использовании данной схемы защиты.

Powerful vertical pipes are commonly applied for mine water drainage installations. The danger of a hydraulic shock arises in them at sudden stopping of the pump. In these conditions the hydraulic diode fixed, for example, in the middle of the pipe can protect from dangerous oscillations of pressure. The most acceptable type of the diode is a jet vortex diode. The main difficulty in modeling the transition process in a vertical pipe with a jet diode is its substantial inertia. The problem was solved by introducing a local coordinate system into the calculation program for the period of the presence of the reverse fluid flow. The main parameters of the vortex diode determining its ability to effectively dampen pressure surges should be considered as the ratio of the inverse hydraulic resistance and the direct resistance, the direct hydraulic resistance and the acceleration time of the liquid (time constant). It is confirmed that the inertial properties of the diode as a whole have a negative impact on the quality of controlled transient process. It is always possible to damp the water hammer in a drainage installation by changing the direct resistance of the vortex diode; however, this will increase the unit energy cost of fluid transfer. The developed mode can be applied for determining the proportions of the rotational diode and for calculating the energy losses which can arise when using the given protection scheme.
Choosing main parameters of vortex diode to prevent water hammer in vertical pipes
Keywords: водоотливная установка; защита; напорный трубопровод; моделирование; вихревой гидравлический диод; drainage installations; protection; discharge pipe; water hammer; vortex diode